Indonesian Slang: Translation Strategies and Accuracy Assessment in the Pasutri Gaje Webtoon’s English Fan Translations - Megalasari, Reviartery Intan; Putri, Astari Amalia (Journal of Language, Literature and Teaching, 2024)
This study aims to analyze the translation strategies used by fans translation translators in translating Indonesian slang with no direct equivalents in “Pasutri Gaje” webtoon into English based on Mona Baker’s theory (2018) and evaluate the translation quality in terms of accuracy using parameters of accuracy developed by Nababan et al. (2012). This research aims to find an effective approach in translating Indonesian slang with no direct equivalents into English, ensuring that the original meaning and nuances of the “Pasutri Gaje” webtoon are well conveyed to the target audience. This study identifies 7 out of 8 translation strategies applied by fans translation translator, including 25 data of translation by a more general word ( 9%), 22 data of translation by a more neutral/less expressive word (8%), 45 data of translation by cultural substitution (16%), 2 data of translation using a loan word or loan word plus explanation (1%), 39 data of translation by paraphrase using the related word, 114 data of translation by paraphrase using the unrelated word (42%) and 27 data of translation by omission (10%). The accuracy analysis found that 118 data (43%) are classified as accurate, 68% data (25%) as less accurate, and 88 data (32%) as inaccurate.